Anti-cancer potential of agarwood distillate - Abbas, Phirdaous; Hashim, Yumi Zuhanis Has-Yun; Amid, Azura; Mohd. Salleh, Hamzah; Jamal, Parveen; Jaswir, Irwandi (Journal of Pure and Applied Microbiology, 2014)
Agarwood or Gaharu by definition is the resin impregnated heartwood that produces unique aromatic scent when burnt. Apart from religious rituals and perfumes, agarwood has also been used as traditional medicines leading to the interest of this study which is to screen for anti-cancer properties. In this study, agarwood water distillate (hydrosol) obtained from distillation of agarwood (resin) were screened against MCF-7 cells, which are commonly used as in vitro model for breast cancer and VERO cells (normal cells). Distillate samples were collected, diluted and directly subjected to three anti-cancer screening assays (cell attachment assay, cell viability assay and sulforhodamine B assay). It was found that agarwood distillate possesses anti-cancer activity and exerts no significant effects on normal cells. This warrants further investigation with potential development of alternative remedy against cancer while adding more value to the agarwood industry.